2018
DOI: 10.1088/1361-6595/aaa868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma-induced surface charging on catalytic processes: application to CO2activation

Abstract: Understanding the nature and effect of the multitude of plasma-surface interactions in plasma catalysis is a crucial requirement for further process development and improvement. A particularly intriguing and rather unique property of a plasma-catalytic setup is the ability of the plasma to modify the electronic structure, and hence chemical properties, of the catalyst through charging, i.e., the absorption of excess electrons. In this work, we develop a quantum chemical model based on density functional theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 76 publications
0
80
1
Order By: Relevance
“…However, plasma-induced modification of the electronic properties may lead to new catalyst systems. Bal et al [71] investigated supported single-atom catalysts containing Ti, Ni or Cu and reported based on a quantum-chemical model that negative surface charges not only improve the reductive potential of the catalysts, but also change their relative activity. Furthermore, the trapped surface charges initiate the formation of streamers as the trapped surface charges are released by photons emitted from a single filament [72].…”
Section: Plasma-assisted Catalysis: Principles and Interactionsmentioning
confidence: 99%
“…However, plasma-induced modification of the electronic properties may lead to new catalyst systems. Bal et al [71] investigated supported single-atom catalysts containing Ti, Ni or Cu and reported based on a quantum-chemical model that negative surface charges not only improve the reductive potential of the catalysts, but also change their relative activity. Furthermore, the trapped surface charges initiate the formation of streamers as the trapped surface charges are released by photons emitted from a single filament [72].…”
Section: Plasma-assisted Catalysis: Principles and Interactionsmentioning
confidence: 99%
“…It is also possible that the addition of electrons can affect the bonding between a molecular adsorbate and the surface creating repulsive interactions leading to desorption. Bal et al [53] have used density functional theory to look at the effect of negative surface charging of a catalyst exposed to a plasma. They examined the activation of CO 2 on transition metal/alumina catalysts finding that the charging significantly enhances the dissociation of the CO 2 to CO by improving the reductive power of the metal and that the magnitude of this effect differs for different metals.…”
Section: The Catalytic Landscape As Seen By a Plasma Dischargementioning
confidence: 99%
“…Using density functional theory (DFT) calculations, we have already shown that the presence of excess electrons improves the activation of CO2 on supported transition metal clusters 21,22 . In these works, however, we did not attempt to disentangle the role of electric field and surface charge.…”
Section: Introductionmentioning
confidence: 99%